Determinan Minat Wisatawan Muslim Dalam Berkunjung Ke Negara Non-Muslim (Studi Kasus: Masyarakat Muslim Jawa Barat) - Cupian Cupian; Syifa Rizkia Nurfitriani; Muhammad Fajri; Sarah Annisa Noven (Jurnal Ilmiah Ekonomi Islam, 2023)
This study aims to find out the factors that influence the intention of West Java Muslim tourists in visiting non-Muslim countries. The method used in this study is quantitative descriptive method, with a research sample of 400 West Java Muslim communities without a certain age restriction taken using purposive sampling techniques. The data was collected through questionnaires and analyzed using partial least square – structural equation modeling (PLS-SEM) method and processed using SmartPLS 3.3.3 application. The results of this study showed that the level of religiosity of respondents indirectly through the perception of Islamic values and the perception of halal risk has a significant influence on the intention of Muslim tourists in visiting non-Muslim countries. However, the perception of halal value and risk cannot directly affect the intention of Muslim tourists significantly. While the experience does not have a significant influence on intentions, and attitudes is a variable that has the most influence on the intentions of Muslim tourists.